SETTLEMENT OF CORRUPTION CONNECTION CASES FROM THE PERSPECTIVE OF GENERAL CRIMINAL AND MILITARY CRIMES - Irwansyah Irwansyah; Mustamam Mustamam; Cut Nurita (LPPM YPITI, 2026)
Corruption can be committed by any community. It is possible to do so by members of the TNI together with civilians, who must be formally tried legally in the connectivity court. Based on the research, it can be concluded that the mechanism for handling connectivity cases in corruption cases is specifically for the investigation of connectivity cases, carried out by the Connectivity Investigation Permanent Team as stipulated in Article 89 of the Criminal Procedure Code and article 198 paragraph (2) of Law Number 31 of 1997 concerning Military Justice, namely general judicial investigators as referred to in article 6 of the Criminal Procedure Code, consisting of State Police Officials of the Republic of Indonesia, and certain Civil Servant Officials (PPNS) who are given special authority by law, Military Police and Military Inspectors or High Military Inspectors. The obstacle to resolving corruption crimes through the connectivity court is too complicated and long a procedure because the formation of a connection case investigation team was formed based on a joint decree between the TNI Commander and the Supreme Court. In addition, the Supreme Court and the Minister of Defense must also reciprocally propose the appointment of member judges who will handle connectivity cases.